2021
DOI: 10.1186/s13054-021-03480-1
|View full text |Cite
|
Sign up to set email alerts
|

Acute cholangitis in intensive care units: clinical, biological, microbiological spectrum and risk factors for mortality: a multicenter study

Abstract: Background Little is known on the outcome and risk factors for mortality of patients admitted in Intensive Care units (ICUs) for Acute cholangitis (AC). Methods Retrospective multicenter study included adults admitted in eleven intensive care units for a proven AC from 2005 to 2018. Risk factors for in-hospital mortality were identified using multivariate analysis. Results Overall, 382 patients were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…3 The previous studies on microbial profile in BTIs with bacteremia were summarized in Table 7. 10,11,[17][18][19] The proportion of causative pathogens varied between studies, but their distribution was similar. The most common Gramnegative bacteria were E. coli (20.5% to 52.3%), followed by Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%
“…3 The previous studies on microbial profile in BTIs with bacteremia were summarized in Table 7. 10,11,[17][18][19] The proportion of causative pathogens varied between studies, but their distribution was similar. The most common Gramnegative bacteria were E. coli (20.5% to 52.3%), followed by Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors of 30-day mortality were underlying malignancies and acute renal failure requiring emergent hemodialysis other than the APACHEII score. Delayed biliary decompression >12–48 h in acute severe cholangitis patients is a risk factor for mortality [ 2 , 23 ]. Early biliary drainage occurring within 24 h shortens the length of ICU stay but does not improve survival [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found no statistical differences in mortality rate between the EBD and PTBD groups. This indicated that infection control with adequate biliary drainage is more critical than which drainage method is implemented [ 23 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who need procedures done at the bedside require extensive coordination and preparation to move equipment quickly. Since timing can be a priority in an acutely sick patient, the endoscopist may not have all the tools necessary to complete the procedure safely and promptly outside of the gastroenterology suite [ 24 - 26 ]. These can contribute to more complications, subsequently causing the increased lengths of stay and higher total charges seen in our study.…”
Section: Discussionmentioning
confidence: 99%